Metode Pembelajaran Karya Wisata Terhadap Keterampilan Menulis Teks Laporan Hasil Observasi Siswa - Hadi, Ihsan; Dani, Refril (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The field trip learning method is a learning method that provides students with the opportunity to explore the surrounding environment as a source of learning. Students are required to be able to construct knowledge independently through the exploration process in order to achieve learning objectives, especially in terms of observation report writing skills. This study aims to see the effect of the field trip learning method on the observation report writing skills of grade VII junior high school students. The study used a quasi-experimental design. The study population was 151 students. Sampling was carried out by simple random sampling. Data collection used a performance test instrument. Data analysis and discussion were descriptive-analytical with the concept of experimental research. The results of the hypothesis test revealed that there was an effect of the field trip learning method on the learning outcomes of students' observation report writing skills than using conventional learning methods.